Determination of Aflatoxin Concentrations in Cereals and Legumes Marketed in Zaria Metropolis, Kaduna State, Nigeria - Shitu, S.; Attahiru, M.; Umar, H. (UMYU Journal of Microbiology Research, 2021)
Aflatoxins are group of secondary fungal metabolites produced by Aspergillus species, such as Aspergillus flavus and Aspergillus parasiticus. The aflatoxin producing moulds can grow on cereals and legumes in the field, poorly dried harvested crops in storage, processed food, and feed products. The study was carried out with the aim to determine the level of aflatoxin contamination of cereals grain and legumes in Zaria metropolis, Kaduna State, Nigeria. Ninety